103PComparative study of RT-qPCR- and NGS- based platforms for circulating human microRNA biomarker detection. (7th November 2019) - Gargiuli, C; Dugo, M; De Cecco, L; Iannò, M F; Mariancini, A; Marchesi, E; Mancinelli, E; Micali, A; Boeri, M; Sozzi, G; Sensi, M
Abstract: Background: Circulating microRNAs (cmiRNAs) are emerging as promising non-invasive biomarkers in cancer for their diagnostic, prognostic and predictive potential. Several platforms have been developed to determine the presence of miRNAs in biological fluids, including specific focus panels. In this pilot study, we aimed at comparing different platforms for detection of cmiRNAs against the same cohort of plasma samples alongside RT-qPCR and NGS technologies. Methods: RNA was isolated from 24 plasma samples obtained from lung cancer patients (n = 12, including one replicate) and healthy heavy smokers (n = 12, including two replicates). Six different platforms were used to detect human cmiRNAs. Five of them were high-throughput technologies, three RT-qPCR-based (TaqMan OpenArray and TaqMan OpenArray Advanced MicroRNA Panels by ThermoFisher; miRCURY LNA miRNA miRNome PCR panel by Qiagen) and two NGS-based (EdgeSeq miRNA byHTG and QiaSeq miRNA by Qiagen). The sixth platform, RT-qPCR-based and serum/plasma focused, was TaqMan Advanced miRNA Human Card by ThermoFisher. Samples were handled according to manufacturer's instructions and data from each platform were analyzed using specific recommended thresholds. Results: Selecting cmiRNAs yielding signals above background, we highlighted a subset commonly detected by all platforms. Strong concordance and correlation coefficients (>0.8) between the three replicate samples were obtained in most platforms, from independent RNA extractions. For each sample, the number of cmiRNAs detected ranged from 90 to 140. We found that inter-platform correlations were highest for platforms based on similar chemistry and assay design. Between lung cancer patients and healthy donors, few deregulated miRNAs could be however commonly detected by all platforms and studies are ongoing to elucidate their role. Conclusions: This study is one of the first comparing RT-qPCR, NGS-based high-throughput and serum/plasma focused platforms for human cmiRNA biomarker detection. Advantages and limits of all platforms and data on intra- and inter- reproducibility will be presented to help investigators in identifying technologies better suited for cmiRNAs screening or validation in clinical cohorts. Legal entity responsible for the study: The authors. Funding: Italian Association for Cancer Research (AIRC, Special Programme "5 X 1000", ED No12162) to GS and MS and by Italian Ministry of Health (funds obtained through an Italian law that allows tax-payers to allocate the "5 × 1000" share of their payments to research) to LDC. Disclosure: All authors have declared no conflicts of interest.